Damming an electronic energy reservoir: ion-regulated electronic energy shuttling in a [2]rotaxane. Issue 26 (14th June 2021) - Yu, Shilin; Kupryakov, Arkady; Lewis, James E. M.; Martí-Centelles, Vicente; Goldup, Stephen M.; Pozzo, Jean-Luc; Jonusauskas, Gediminas; McClenaghan, Nathan D.
Abstract : Delayed emission due to reversible electronic energy transfer (REET) between chromophores in the axle and macrocycle components of a rotaxane is demonstrated. The REET process can be modulated by metal ion binding in the cavity of the rotaxane. Abstract : We demonstrate the first example of bidirectional reversible electronic energy transfer (REET) between the mechanically bonded components of a rotaxane. Our prototypical system was designed such that photoexcitation of a chromophore in the axle results in temporary storage of electronic energy in a quasi-isoenergetic "reservoir" chromophore in the macrocycle. Over time, the emissive state of the axle is repopulated from this reservoir, resulting in long-lived, delayed luminescence. Importantly, we show that cation binding in the cavity formed by the mechanical bond perturbs the axle chromophore energy levels, modulating the REET process, and ultimately providing a luminescence read-out of cation binding. Modulation of REET processes represents an unexplored mechanism in luminescent molecular sensor development.